THE EFFECT OF USING COOPERATIVE SCRIPT ON STUDENT’S READING COMPREHENSION AT GRADE ELEVENT OF SMA NEGRI 2 PEMATANGSIANTAR - Herman Herman; Enji Putri Ivantara; David Berthony Manalu (Acitya: Journal of Teaching and Education, 2020)
This study is about the effect of Cooperative Script on students’ reading comprehension. Problem raised in this research was: What is the effect of using Cooperative Script on student’s reading comprehension at Grade eleven of SMA Negeri 2 Pematangsiantar? To answer the question, the researchers used some theories such as: Harmer (2007), Bolukbas, Keskin, and Polat (2011), Herman (2014) and Barker (2000). Experimental design was conducted to this research. The population of the study was the 2019/202 academic year firstsemester grade XI students of SMA Negeri 2 Pematangsiantar. The samples were two classes, namely XIPMIA3 and XIPIS 1, with the total was 68 students selected by applying random sampling. The sample was divided into two groups. Experimental group (XI PIS 1) was taught by applying Cooperative Script Method while the control group (XI PMIA 3) was taught by applying explaining method. There were two data used in this research. They were pre-test and post-test. The data were analyzed by using t-test formula to show the effect of applying Cooperative Script Method on students’ reading comprehension. After analyzing the data, the finding indicates that t-observed was higher than t-table (6.263 > 1.668)) with the degree of freedom (df) = 66. It means that applying Cooperative Script Methodhas significantly affected students’ reading comprehension.